The 5-5-2 criteria for biliary cannulation and post endoscopic retrograde cholangiopancreatography complications: Experience in a reference hospital, Peru - Quiroga Purizaca, Wilmer Gustavo (2023)
The European Society for Gastrointestinal Endoscopy (ESGE) defines “difficult biliary cannulation” by the presence of one or more of the following: more than 5 contacts with the papilla, more than 5 minutes attempting to cannulate, or inadvertent cannulation of the pancreatic duct in 2 or more times (5-5-2 criteria), recommending these cut-off points to perform advanced cannulation techniques in order to reduce the rate of post-ERCP adverse events. Our objective was to evaluate the performance of the 5-5-2 criteria and their association with post-ERCP complications in a reference hospital in Peru. We performed a prospective analytical case-control study and 120 patients who underwent ERCP were enrolled. The case group included 30 patients who met at least one of the 5-5-2 criteria and the control group included 90 patients without any of these criteria. The ERCP- related complications in both groups and their association with each of the 5-5-2 criteria were compared. The ERCP-related complications that occurred were post-ERCP pancreatitis (6.6% in the case group vs. 3.3% in the control group), bleeding (3.3% controls vs. 0% cases) and perforation (1.1% controls vs. 0% cases); no statistically significant differences were observed. The criterion of 2 or more unintended cannulations to the pancreatic duct showed a significant association (OR= 10.29, CI: 1.47-71.98; p= 0.005) with the incidence of post-ERCP pancreatitis. The criteria 5 minutes and 5 attempts were not associated with post-ERCP complications. In conclusion, among 5-5-2 criteria only the unintended cannulation of 2 or more times into the pancreatic duct was associated with an increased risk of post-ERC pancreatitis. The time and number of attempts criteria could be cautiously expanded without increasing the rate of post-ERCP complications.